Forming competitiveness of a specialist to-be in the youth policy system of the North-Caucasus Federal University - M. I. Kochergin (Вестник Северо-Кавказского федерального университета)
Introduction. The relevance of the study is due to the growing interest of the state and modern society in forming a highly qualified professional who is competitive both in Russian and in the global labor market. In connection with this the task arises of finding additional forms, means and technologies for developing those qualities that are necessary for increasing the competitiveness of a specialist to-be. The author focuses on this topic since there is lack of knowledge of the problem of the influence of student participation in the activities of university public associations on the process of developing the competitive qualities of specialists to-be.The goal is to identify and present personal and professional qualities of a specialist to-be necessary for an employer, which are formed in the space of activity of student public associations.Materials and methods. To achieve this goal, the following methods were used: theoretical analysis and generalization of regulatory documents, scientific, educational and methodological materials, Internet portals, a survey using the «I am a leader» test method, and statistical processing of data obtained during the study.Results and discussion. The study revealed the qualities most sought after by employers, such as teamwork, creative and organizational skills, and communication skills. The result of the experiment showed that students involved in the systematic activities of student associations have a significantly higher level of development of these qualities compared to those who ignore participation in socially significant development work.Conclusion. Based on the results of the study, we can conclude that systematic activity of students in associations contributes to the development of their competitiveness and demand in the modern labor market, due to a higher level of development of the qualities, which are in demand. The results obtained allow us to specify and anticipate the effectiveness of the institution of public associations in the university in the vector of forming a competitive specialist and confirm the foundations of the author’s dissertation research. The study of this problem will continue as there remain unresolved issues indicated in the conclusion of the main text.